Simulation of Impinging Cooling Performance with Pin Fins and Mist Cooling Adopted in a Simplified Gas Turbine Transition Piece - Tao Xu; Hang Xiu; Junlou Li; Haichao Ge; Qing Shao; Guang Yang; Zhenglei Yu (Advances in Mathematical Physics)
The gas turbine transition piece was simplified to a one-four cylinder double chamber model with a single row of impinging holes in the outer wall. Heat transfer augmentation in the coolant chamber was achieved through the use of pin fin structure and mist cooling, which could increase the turbulence and heat transfer efficiency. The present research is focused on heat transfer and pressure characteristics of the impinging cooling in the coolant chamber using FLUENT software. With the given diameter of impinging hole, pin fin diameter ratios D/d have been numerically studied in ranges from 1 to 2. Three different detached L were simulated. The impinging cooling performance in all cases was compared between single-phase and two-phase (imported appropriate mist) flow in the coolant chamber. All the simulation results reveal that the factors of L and D/d have significant effects on the convective heat transfer. After the pin fin structure was taken, the resulting temperature decrease of 38.77 K at most compared with the result of structure without pin fins. And with the mist injecting into the cooling chamber, the area weighted average temperature got a lower value without excess pressure loss, which could satisfy the more stringent requirements in engineering.